Randomized dose-finding clinical trial of oncolytic immunotherapeutic vaccinia JX-594 in liver cancer - Heo, Jeong; Reid, Tony; Ruo, Leyo; Breitbach, Caroline J; Rose, Steven; Bloomston, Mark; Cho, Mong; Lim, Ho Yeong; Chung, Hyun Cheol; Kim, Chang Won; Burke, James; Lencioni, Riccardo; et al. (Nature medicine, 2013)
Oncolytic viruses are under development for tumor treatment. David Kirn and colleagues now report their results of a randomized phase 2 dose-finding trial of JX-594, an oncolytic immunotherapeutic vaccinia virus, in patients with advanced hepatocellular carcinoma. The study shows that high-dose JX-594 was associated with significantly improved overall survival and induced radiographic responses and antitumor immunity. Oncolytic viruses and active immunotherapeutics have complementary mechanisms of action (MOA) that are both self amplifying in tumors, yet the impact of dose on subject outcome is unclear. JX-594 (Pexa-Vec) is an oncolytic and immunotherapeutic vaccinia virus. To determine the optimal JX-594 dose in subjects with advanced hepatocellular carcinoma (HCC), we conducted a randomized phase 2 dose-finding trial ( n = 30). Radiologists infused low- or high-dose JX-594 into liver tumors (days 1, 15 and 29); infusions resulted in acute detectable intravascular JX-594 genomes. Objective intrahepatic Modified Response Evaluation Criteria in Solid Tumors (mRECIST) (15%) and Choi (62%) response rates and intrahepatic disease control (50%) were equivalent in injected and distant noninjected tumors at both doses. JX-594 replication and granulocyte-macrophage colony-stimulating factor (GM-CSF) expression preceded the induction of anticancer immunity. In contrast to tumor response rate and immune endpoints, subject survival duration was significantly related to dose (median survival of 14.1 months compared to 6.7 months on the high and low dose, respectively; hazard ratio 0.39; P = 0.020). JX-594 demonstrated oncolytic and immunotherapy MOA, tumor responses and dose-related survival in individuals with HCC.